Systém odměňování zaměstnanců ve vybrané společnosti a návrh jeho změn - Štercová, Tereza (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Diplomová práce se zabývá systémem odměňování zaměstnanců ve vybrané společnosti. Teoretická část popisuje základní pojmy týkající se oblasti odměňování zaměstnanců. Analytická část hodnotí současný systém odměňování zaměstnanců ve společnosti, včetně vnitřních a vnějších vlivů působících na daný systém. Na základě provedených analýz jsou zaměstnavateli navrženy změny stávajícího systému odměňování s cílem vylepšit současný stav.

The master's thesis deals with the system of remuneration for employees in the selected company. The theoretical part defines the basic terms related to the employee remuneration. The analytical part evaluates the current employee remuneration system in the company, including internal and external factors influencing the system. Based on this analysis, changes to the remuneration system are proposed to the employer in order to improve the current situation.
Employee Remuneration System in the Selected Company and Proposal of its Changes
Keywords: řízení lidských zdrojů; zaměstnanec; zaměstnavatel; odměňování zaměstnanců; celková odměna; mzda; zaměstnanecké benefity; human resources management; employee; employer; remuneration of employees; total remuneration; wage; employee benefits